Conflict, Economic Development and Peacebuilding in the African Context - Olatayo, Samuel (African Journal of Stability and Development (AJSD), 2025)
The intricate nexus between conflict, economic development, and peace presents a defining challenge for the African continent. While often analysed through simplistic lenses of resource scarcity or ethnic rivalry, this paper argues that the relationship is a self-reinforcing cycle driven by historical legacies, institutional frailties, and the political economy of violence. Drawing on contemporary case studies and theoretical frameworks, it posits that colonial-era policies established patterns of regional inequality and weak state structures, which post-independence governments often exacerbated through resource dependency and systemic corruption. This has created environments where conflicts fueled by economic marginalisation stifle the investment, human capital, and stability necessary for development, thereby perpetuating conditions for further violence. Moving beyond diagnostic analysis, this paper explores the imperative of transformative peacebuilding. It concludes that sustainable peace is contingent upon moving beyond mere conflict resolution to actively fostering distributive justice, accountable governance, and resilient, diversified economies that address the root causes of instability.